Characteristics of paediatric out-of-hospital cardiac arrest in the United States. (August 2020) - Okubo, Masashi; Chan, Hei Kit; Callaway, Clifton W.; Mann, N. Clay; Wang, Henry E.
Abstract: Background: The absence of nationwide surveillance data on out-of-hospital cardiac arrest (OHCA) in the United States (US) limits understanding of the epidemiology of paediatric OHCA. We investigated the national characteristics of paediatric OHCA using the National Emergency Medical Services Information System (NEMSIS). Methods: We conducted a cross-sectional study using the 2016 NEMSIS dataset, a national registry of emergency medical services (EMS) activations at 46 states in the US. We included paediatric patients (age <18 years) with "9-1-1" EMS responses to OHCA. We defined OHCA as (a) presence of cardiac arrest; (b) EMS reported initiation of cardiac arrest resuscitation; (c) performance of chest compressions; or (d) performance of defibrillation. We reported the incidence and characteristics of paediatric OHCA, stratified by age group: <1 year: infants, 1–5 years: young children, 6–12 years: older children, and 13–17 years: adolescents. Results: Among 1, 531, 469 paediatric EMS responses, we identified a total of 23, 514 EMS responses to paediatric OHCA (95% confidence interval [CI], 23, 217–23, 814), incidence of 15.4 per 1000 paediatric EMS responses (95% CI, 15.2–15.5), and estimated national incidence of 37.9 per 100, 000 child-years (95% CI, 37.4–38.4). Among 23, 514 EMS responses to paediatric OHCA, we observed 4515 (19.2%) of EMS responses in infants, 5588 (23.8%) in young children, 4976 (21.2%) in older children, and 8435 (35.9%) in adolescents. Conclusion: Using data from the NEMSIS, we estimate that there are over 23, 000 annual paediatric OHCA in the US. These data provide key insights of paediatric OHCA in the US.